2021
DOI: 10.3390/toxins13120889
|View full text |Cite
|
Sign up to set email alerts
|

Triceps Surae Muscle Characteristics in Spastic Hemiparetic Stroke Survivors Treated with Botulinum Toxin Type A: Clinical Implications from Ultrasonographic Evaluation

Abstract: Equinovarus foot is one of the most commonly spasticity related conditions in stroke survivors, leading to an impaired gait and poor functional performances. Notably, spastic muscles undergo a dynamic evolution following typical pathophysiological patterns. Botulinum Neurotoxin Type A (BoNT-A) is the gold standard for focal spasticity treatment, and ultrasound (US) imaging is widely recommended to guide injections and monitor muscle evolution. The role of BoNT-A in influencing muscle fibroadipose degeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In 2021, Battaglia et al investigated the effects of BoNT-A by conducting a cross-sectional observational study on 53 spastic hemiparetic stroke survivors. 37 They concluded that BoNT-A does not seem to influence muscle degeneration and that EI increase appears to be primarily related to spastic muscle evolution and functional impairment. Interestingly, in subjects with preserved walking capability and lower spasticity grade, an increase in EI of the medial gastrocnemius was observed in the paretic limb alone, but in patients with impaired gait and more severe spasticity, similar US changes were observed in both calves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2021, Battaglia et al investigated the effects of BoNT-A by conducting a cross-sectional observational study on 53 spastic hemiparetic stroke survivors. 37 They concluded that BoNT-A does not seem to influence muscle degeneration and that EI increase appears to be primarily related to spastic muscle evolution and functional impairment. Interestingly, in subjects with preserved walking capability and lower spasticity grade, an increase in EI of the medial gastrocnemius was observed in the paretic limb alone, but in patients with impaired gait and more severe spasticity, similar US changes were observed in both calves.…”
Section: Resultsmentioning
confidence: 99%
“… 75 Echogenicity can also be assessed qualitatively 36 , 44 ,49,67-71, 76 or quantitatively with software-generated gray-scale score and pixel analysis. 37 , 41 ,52,61,69, 75 Brightness or B-mode US can be used to visualize tissues with varying sonoacoustic properties; these properties in turn determine the number of echoes returning to the transducer. Structures will appear bright or hyperechoic when they are highly reflective of sound waves, whereas they will appear dark or hypoechoic when they reflect few sound waves to the transducer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BoNT-A provides transient and reversible presynaptic chemodenervation on the neuromuscular plate. Moreover, BoNT-A shows an optimum safety profile and effectiveness in reducing pain, improving walking ability, mobility, nursing procedures, activities of daily living, and ultimately QoL ( 14 ), without significantly altering muscle quality ( 15 ). However, the current literature is mainly based on post-stroke spasticity (PSS) ( 16 , 17 ), whereas it is still limited in case of other clinical conditions related to non-stroke spasticity (NSS), such as SCI, TBI, and MS, even though spasticity is a major concern for rehabilitation in these patients.…”
Section: Introductionmentioning
confidence: 99%